Two new tardigrade species (Echiniscidae and Doryphoribiidae) from the Salta province (Argentina) - Rocha, Alejandra; Doma, Irene; Reyes, Andrea Gonzalez; Lisi, Oscar (Zootaxa, 2020)
Tardigrades from Argentina are poorly known. Two new species from the Salta province are described in the present contribution: Pseudechiniscus saltensis sp. nov., and Doryphoribius cephalogibbosus sp. nov. The former species belongs to the novaezeelandiae group and, apart from the nominal species of the group, it is similar to nine congeneric species by the following characters: the absence of spines on legs I and lateral papillae, the scapular plate with a transversal fold, the presence of projections at the posterior margin of the pseudosegmental plate, caudal plate not faceted, and cuticular ornamentation in the form of heads (capituli) of endocuticular pillars, protruding through epicuticle and joined by striae. However, the new species differs from all of them in important qualitative (e.g. colour, different division of plates, details of cuticular ornamentation, claws etc.) and morphometric characters. The new species exhibits a unique morphology of gonopore and anus. Doryphoribius cephalogibbosus sp. nov., by the presence of two macroplacoids, dorsal gibbosities, and inhabiting terrestrial environment, belongs to the flavus group and differs from all members of the group in having ten, instead of nine, rows of gibbosities (X:2-4-6- 6-6-6-6-4-2-2+2[LI–III]), with as a peculiar exclusive character, the presence of the two cephalic gibbosities, never reported in other Doryphoribius species. Moreover, the new species differs from the other species of the group by morphometric and more detailed morphological characters. The new species description also gave an occasion to discuss the issue of gibbosity arrangement in other species and address the morphology of claw accessory points.